Simulation Modeling System in Determining the Amount of Oil Inventory - Okta Veza; Larisang; Albertus L. Setyabudhi; Nofri Yudi Arifin; Sherly Agustini (Journal of Computer Networks, Architecture and High Performance Computing, 2023)
Currently, XYZ Gas Stations, in carrying out fuel sales activities, have not yet used a simulation of calculating fuel supply needs at gas stations which functions to support decision making by the leadership, this causes frequent stock shortages at each XYZ gas station branch. because of that the authors are interested in creating a modeling system for calculating fuel inventory simulations using the Monte Carlo method and the LCM pattern. The purpose of this research is to produce a simulated calculation of the supply of purchased fuel so that management knows how much stock of fuel must be provided at each gas station and also to prevent empty fuel stocks at each gas station in the XYZ branch. The data collection methods used in this study were interviews, observations, and literature studies. The system is designed using the JAVA Programming Language. The data processed in this study is transaction activity data for January and February 2022 to determine the amount of inventory that must be provided in March 2022. The final results of the data processing that has been carried out with the trial purchase data transactions for the two current months, namely January and February 2022 to get the simulation results of fuel oil (BBM) supplies in March whose activation has been running with simulation predictions using the Monte Carlo Algorithm.